KEBEBASAN BERPENDAPAT PADA MEDIA JEJARING SOSIAL - Rahmad Arsyad; Muhammad Nadjib (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2011)
Abstract This research aims to assess and analyze the form of free speech on Facebook Social Media Networking from a friendship social networking into a resistance social networking. This study investigated the form of free speech in the Facebook groups discourse as an expression of emerging resistance to shed public opinion in addressing the various social and political conditions in Indonesia. Thee method in this research is using Norman Fairclough Critical Discourse Analysis which divides the discourse analysis model into three dimensions, namely: text, discourse practices, and sosiocultural practice. In addition to data collection methods used were interviews to view social cognition resistence movement on Facebook. The result showed that the form of the free speech on the Facebook as a social network of friend have experienced social reconstruction by the user into an alternative media in voicing their opinion that has not found the “canalization aspirations.” Inhibition of the freedom of public opinion through instruments such us as the council representative of the aspirations of the people, government and mass media have been encouraging people to vote facebook as a means of delivering the aspirations of an easy and widely accessible.Abstrak penelitian ini dimaksudkan untuk mengakses dan menganalisis bentuk kebebasan berbicara (berpendapat) dalam Facebook, mulai dari fungsinya sebagai jejaring sosial pertemana sampai pada jejaring perlawanan. Studi ini menyelidiki kebebasan berpendapat pada kelompok-kelompok facebook, utamanya dalam wacana penolakan sebagai bentuk pendapat umum mengenai kondisi sosial politik di Indonesia. Metode yang digunakan dalam penelitian ini memakai analisis wacana kritis dari Norman Fairclough yang terdiri atas tiga dimensi, yaitu: teks, wacan , sosial budaya. Pengumpulan data dilakukan dengan metode wawancara dari aspek kognisi sosial melalui media alternative yang selama ini tidak bisa mereka salurkan melalui lembaga-lembaga seperti Dewan Perwakilan Rakyat, Pemerintah, atau media massa. Keterbatasan itu mendorong mereka menggunakan media alternative facebook untuk menyalurkan aspirasi mereka lebih mudah dan bisa diterima secara luas.